Determining The Location of Charging Station Facilities in Surakarta City Using Gravity Location Models - Nugrahadi, Bekti; Trisna Devi, Anita Oktaviana; Amalia, Nasyita Vivi; Primasanti, Yunita (Universitas Mercu Buana, 2024)
Environmental problems caused by motorized vehicles are in the spotlight in the modern era. Various methods have been taken to reduce the environmental impact caused by motorized vehicles. One way to reduce the negative environmental impacts caused by motorized vehicles is to use environmentally friendly vehicles, namely electric vehicles. Presidential Regulation No. 55 of 2019 encourages the electrification of motorized vehicles in Indonesia. To support these regulations, there needs to be infrastructure for the smooth and easy use of electric vehicles. This research aims to determine the optimal charging station location in the city of Surakarta using gravity location models to support the implementation of the government program for vehicle electrification. Based on the calculations carried out, Banjarsari is the optimal point for the location of the charging station.